Die Moerder sind unter uns . The Murderers Are Among Us - Staudte, Wolfgang (Germany, 1948)
Duration: 01:20:00 Ranked by critics as one of Germany’s most important films, "The Murderers Are Among Us" offers a wrenching look at history and humanity. The first feature film produced in Germany after World War II, it is set in Berlin just after the surrender, and the city is still being battered by air raids. The characters move through the half-destroyed husks of old buildings, and even simple acts like serving a meal at a table take on new meaning as the people try to put their lives back together. Susanne Wallner is a concentration camp survivor, eager to taste life again after her living death. She returns to Belin from the concentration camp to discover that someone else had moved into her apartment. Dr. Hans Mertens who had taken up residence in Susanne's place, is a former German officer, unable to live with the guilt of what he and his former comrades have done. The two must quite literally learn to live side by side as they come to terms with the past and start to look toward the future. The film is beautifully and sensitively made, and possesses a shining optimism that is surprising for its time.